Corpo-revolução, moda (in)adequada: o corpo lgbtq e suas rupturas na cultura normativa - Borsa, Angelo Nunes de Oliveira (Universidade do Vale do Rio dos Sinos, 2019)
This research proposes a look LGBTQ person’s body, seen as different from the normative hegemony of sexualities, as a social body, creating meaning and being a creator force of revolutions. Starting from the cultural perspective proposed by Cliffor Geertz, and the thoughts about body, sexuality and gender of third wave feminist Judith Butler, the ritualities that intertwine human relations, the images that permeate the world and our representation as individuals, the body-revolution is conceptualized and organized. Here, through an anthropological look of the LGBTQ person, the body-revolution takes shape and is manifested.
Keywords: Corpo; Cultura; LGBTQ; Ritual; Moda; Body; Culture; Ritual; Fashion